2017
DOI: 10.4085/1062-6050-52.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb and Trunk Biomechanics After Fatigue in Competitive Female Irish Dancers

Abstract: When fatigued, dancers displayed a decline in landing performance in terms of aesthetics as well as increased ankle- and knee-joint loading, potentially exposing them to a greater risk of injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Therefore, it may happen as dancers have to dance for a longer time and cannot pay enough attention to controlling the movements entirely, which may let their limbs move more freely, leading to an energetically more expensive increment in the joints' ROM. Furthermore, Wild et al showed that in the case of Irish dancers, after a certain amount of fatiguing session, the dancers landed with a reduced ankle plantar flexion and external hip rotation and increased hip-adduction alignment [5].…”
Section: Discussion Of the Motion Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it may happen as dancers have to dance for a longer time and cannot pay enough attention to controlling the movements entirely, which may let their limbs move more freely, leading to an energetically more expensive increment in the joints' ROM. Furthermore, Wild et al showed that in the case of Irish dancers, after a certain amount of fatiguing session, the dancers landed with a reduced ankle plantar flexion and external hip rotation and increased hip-adduction alignment [5].…”
Section: Discussion Of the Motion Analysismentioning
confidence: 99%
“…The most dangerous elements for the joints are the leg slamming elements, because they can cause cartilage wear [3,4]. Such folk steps, when the legs are placed forcefully onto the floor, are similar to some steps of Irish folk dances, which have been examined previously from a biomechanical point of view [5].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In marimba performance specifically, torso movements were found to elicit feelings of happiness, sadness, and anger in raters viewing silent performance videos (e.g., Dahl and Friberg, 2007 ). In alternate rhythmic contexts, such as dance, torso movements are also critical for emotional communication (e.g., Wild et al, 2017 ). Overall, the postural sway cluster may reflect an emotionally expressive approach, and therefore was considered to encompass an emotionally vibrant style.…”
Section: Discussionmentioning
confidence: 99%